IMPLEMENTASI DAN ANALISIS UNJUK KERJA JARINGAN OPENSWAN DAN OPENVPN PADA PT RELIANCE - Yulianto, Wahyu Andy; Jusak, Jusak; Mardiana, I Dewa Gede Rai (Journal of Control and Network Systems, 2014)
Virtual Private Network (VPN) is a communications technology that allows connections to and from public network as if working on a private network. By using this technology, users are possible to access files, or even a database server inside the private network. The users are able to access the network using the same settings as they were physically located in a private network.This experiment are intended to get the value of the parameters and analyzing performance of the VPN network. To get these values real computer networks that consists of two VPN gateways equipped with tools and testing applications such as PING, FTP, tcpdump, video streaming (IP CCTV) applications and VoIP (SJPhone) were built.Network performance examination have obtained values of latency, packet loss, bandwidth delay product and bandwidth utilization. It is shown that smaller latency will produce the most efficient bandwidth delay product. At the same time, small value of latency will produce large bandwidth utilization for TCP applications. On the other hand, small value of packet loss will result in large bandwidth utilization for UDP applications.